Pemenuhan Hak Pilih bagi Lanjut Usia (Lansia) yang Mengalami Hambatan Fisik dan Sensorik (Studi Pemilih Lanjut Usia (Lansia) pada Pemilu 2024 di Kabupaten Blitar) - Girlee Geniusy Dinastya Haris; M. Syafi’ie (Fakultas Hukum Universitas Islam Indonesia, 2025)
This study aims to analyze the factors that hinder elderly voters with physical and sensory barriers from exercising their voting rights in the 2024 general election in Blitar Regency, as well as analyze the mechanisms and policies developed to fulfill voting rights for elderly voters who experience physical and sensory barriers in the 2024 election in Blitar Regency. This research uses empirical juridical legal methods with sociological and policy approaches. The results of this study show that the lack of socialization, data collection that is not optimal, and the lack of election service facilities are the main factors that hinder elderly voters with physical and sensory barriers from exercising their voting rights. In addition, the mechanisms and policies developed by the KPU and Bawaslu of Blitar Regency as an effort to fulfill the right to vote for the elderly with physical and sensory barriers through socialization programs and mobile polling stations have not been able to run optimally. This is due to the absence of regulations that strictly regulate the specificity of the elderly with physical and sensory barriers in the implementation of general elections. Therefore, a more detailed policy is needed in terms of data collection, socialization, and voting, so that the political rights of elderly voters with physical and sensory barriers can be fulfilled optimally during general elections.